An Analysis Of Deixis In The Short Story Of ‘Mie Goreng’ - Hafni Hafsah (Syntax Literate, 2022)
The research is about deixis used in a short story entitled 'An Analysis of Deixis in The Short Story of Mie Goreng'. It aims to study the types and meanings of deixis used in the story. The use of deixis in writing of a fiction is important because it can provide suitability and understanding of what the author conveys based on the intended meaning. This short story was obtained online from the internet. The analysis of the data in the text uses descriptive qualitative, where it started with reading and translating the story, then finding and classifying diexis, as well as analyzing the findings by using note-taking techniques. Deixis analysis used Levinson's theory which are 5 (five) types of diction, namely person deixis, time deixis, place deixis, social and discourse deixis. The results of the analysis found all types of deixis in story texts. The highest number of occurrence is in the deixis ‘person’ particularly pronoun ‘I’ where the author uses the first person point of view in telling the story and simultaneously as the leading actor.